2016
DOI: 10.1111/trf.13477
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive description of blood microbiome from healthy donors assessed by 16S targeted metagenomic sequencing

Abstract: We demonstrate that a diversified microbiome exists in healthy blood. This microbiome has most likely an important physiologic role and could be implicated in certain transfusion-transmitted bacterial infections. In this regard, the amount of 16S bacterial DNA or the microbiome profile could be monitored to improve the safety of the blood supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
335
5
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 351 publications
(394 citation statements)
references
References 61 publications
45
335
5
9
Order By: Relevance
“…We performed 16S ribosomal RNA (rRNA) gene sequencing of buffy coat samples and identified 65 genera belonging to four phyla (predominantly Proteobacteria) in this cohort (online supplementary figure 1 and figure 1B). Blood microbiome phylum compositions identified in our study agreed with previous findings investigating the peripheral blood microbiome in buffy coat samples from patients with liver fibrosis2 as well as healthy individuals3 but differed from the gut microbiome measured in faecal samples, where Bacteroidetes and Firmicutes are predominant 2…”
supporting
confidence: 89%
“…We performed 16S ribosomal RNA (rRNA) gene sequencing of buffy coat samples and identified 65 genera belonging to four phyla (predominantly Proteobacteria) in this cohort (online supplementary figure 1 and figure 1B). Blood microbiome phylum compositions identified in our study agreed with previous findings investigating the peripheral blood microbiome in buffy coat samples from patients with liver fibrosis2 as well as healthy individuals3 but differed from the gut microbiome measured in faecal samples, where Bacteroidetes and Firmicutes are predominant 2…”
supporting
confidence: 89%
“…In 2016 Paise et al demonstrated that a diversified microbiome exists in healthy blood. Most of the blood bacterial DNA was found located in the BC (93.74%), while RBCs contain more bacterial DNA (6.23%) than the plasma (0.03%) [14]. A significant number of bacterial species were also detected in the blood of healthy chickens [16] …”
Section: Tedeschi Et Al Reported On Incorporation Of Nucleosides In mentioning
confidence: 85%
“…We note, that some phyla are enriched by the applied resuscitation strategy according to the OTUs combined abundancy (Table 1). Other studies also identified Proteobacteria as predominant in the blood of healthy individuals [14], healthy broilers [16] and cats [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of sequencing fragments was performed by using MiSeq Illumina technology (Illumina Inc.). The 16S targeted sequences were then clustered into operational taxonomic units (OTUs) before taxonomic assignment and analyzed by using the bioinformatics pipeline as described previously (38,39). The OTUs and taxonomy classifications were tabulated, and to account for differences in raw counts across the samples the tables were log normalized by using Equation 1:…”
Section: Experimental Designmentioning
confidence: 99%